KONSEP TAHSINIYAT DALAM MAQASID SYARIAH HUKUM PERKAWINAN - ibnu fauzan; Wasman Wasman (UIN Siber Syekh Nurjati Cirebon, 2022)
Marriage is a bond between a man and a woman as husband and wife who are legal in the eyes of law and religion to form a family (household) that is sakinah, mawadah and warahmah towards a happy family in the world and the hereafter, the basis of marriage is to worship only Allah SWT. Maqasid sharia is a concept that has become an interesting discussion among scholars. This concept was known long before Syatibi, but this concept was very attached to him because he was the first to introduce it completely as a method of legal thought. Substantially maqasid sharia or the purpose of establishing law is nothing but benefit.This type of research is library research (library research), in the sense that all data sources come from written materials in the form of books, documents, magazines and texts that are related to the topic of discussion through a review of various literature related to research which includes primary, secondary data. , dantertier. The data collected, read.The result of this research is that Islamic law has a purpose realizing human benefit (maqasid al-shariah) in the world and happiness in the hereafter. This embodiment is determined by the harmonization of the relationship between humans both individually and collectively, as well as the relationship between humans and their natural surroundings. This relationship is like in marriage, because marriage is a medium for getting to know each other. The true purpose of marriage in Islam is the development of human morality and humanizing it, so that the relationship that occurs between two different genders can build a new life socially and culturally. Maqashid sharia in hifzhu an-Nasl (caring for offspring or honor) is at the hajiat level, then Marriage is a necessity, as a natural human desire to be in pairs.Â